A Scoping Review: Unveiling the Benefits of ACF on Tuberculosis Control - Saroh; Bagoes Widjanarko; Zahroh Shaluhiyah (Universitas Airlangga, 2024)
Background: Tuberculosis (TB) ranks among the top ten infectious diseases and causes of death worldwide. The implementation of active case-finding TV is crucial in achieving the objectives of the World Health Organization’s End TB strategy. Aims: This review aims to determine the role of active case finding in TB control in a community with high-burden TB. Methods: This review used databases Pubmed, Research Gate, Ebscohost, Science Direct, and Scopus. The search for articles used the main keywords community, active case finding, AND tuberculosis. The articles were selected in English, with a five-year time interval between 2019 to 2023. The type of article subject area included medicine, health, health care, environmental science, and social science. The documents were from journals and articles. The text availability was free full text. Results: This review was done on 3.561 articles that were screened and analyzed out of 6 articles. The articles were originated from Cambodia, China, India, and Africa. This scoping review describes the effect of ACF in the community on TB control (cohorts and cross-sectional) in high-burden TB. Results from 5 articles including 6 studies indicated that ACF in the community was significantly associated with TB control. One of the studies revealed that studies in which ACF reported a non-significant association. Conclusion: This review summarized that ACF provides greater benefits than the PCF strategy, especially in high-risk populations and those with limited access to healthcare facilities. It promotes prompt diagnosis and treatment improves treatment outcomes, minimizes health complications, and reduces the social and economic impact of TB.